Genetic analysis for grain yield and its components in barley (Hordeum vulgare L.) - Yadav, Sunil Kumar; Pawar, Kshitiz Kumar; Baghel, Satish Singh; Jarman, Mahesh; Singh, Ashok Kumar (Journal of Cereal Research, 2014)
Fifty two genotypes of barley were investigated for variability, character association and,path analysis for grain yield and its components. The data were recorded for days to 50% fowering, days to maturity, plant height, number of tillers per plant, spike length, grains per spike, 1000 grain weight, biological yield per plant, harvest index and grain yield per plant. Estimates of broad sense heritability were high for all traits except days to maturity, number of tillers per plant and, grain yield per plant. High heritability estimates coupled with moderate genetic advance as percentage of mean were recorded for biological yield per plant, grains per spike, plant height and days to 50% fowering. From path analysis recorded the highest positive direct effect of days to 50% fowering, biological yield per plant and lowest due to days to maturity on grain yield.